Pyrgeuma pyrgodesmoides, n. gen., n. sp., a new millipede from Malaysia with unusual surface structures (Diplopoda, Chordeumatida, Heterochordeumatidae) - Shear, William A. (Zootaxa, 2012)
Pyrgeuma pyrgodesmoides n. gen., n. sp., is described from the Cameron Highlands of Malaysia as the sixth (or possiblyseventh) species and third genus of the millipede family Heterochordeumatidae. The new species is remarkable in its re-semblance to members of the unrelated polydesmidan family Pyrgodesmidae, an interesting case of convergent evolutionin the tropical soil and litter fauna. The dorsal surface of the body is covered in small, curved, spatulate microtrichia and the metzonital setae are reduced to nearly undetectable size.